Comparing the Language Development of Native and Foreign Born Children. - Mick, Jennifer; Endvick, Julie; Heath, Stacy (My University, 2009)
This study compared the language development of one foreign born child to that of two native born children. Researchers followed these children, two males and one female, from 26 to 36 months of age. This research provides insight into this critical period of child development which is predictive of later communication, social-emotional and cognitive skills.
Documenting the Language Development of 2 year Old Children.
Color poster with text and graphs describing research conducted by Julie Endvick, Stacy Heath, and Jennifer Mick, advised by Marie A. Stadler.
Keywords: Language acquisition--Case studies; Children--Language--Case studies; Bilingualism in children--Case studies.; Adopted children--Language--Case studies; Language acquisition--Age factors; English language--Study and teaching (Preschool); Posters